Chihuahua too! Charlie a toy Story / Finn on the Fly / Vampire Dog - Most, Morgan; Mutrux, Chaia; Harding, Zay (Auckland, New Zealand Distributed by Jigsaw Entertainment, 2014)
Chihuahua Too! : When the Fasteners inherit an old family vacation home, they soon realize it's being haunted by their ancestors dog, Sophie. Homer, their golden retriever, befriends Sophie and discovers that she is just looking for a family to love.
Charlie a Toy Story : Get ready for hilarious, fun-filled adventures as 10 year old Caden, along with his best friend and golden retriever, Charlie, protects his dad's toy shop and greatest invention from the town bullies. Filled with warmth and humor, this laugh a minute comedy will reignite your imagination and show you that anything is possibly if you just believe in yourself.
Flinn on the fly : What if your dog became a human? Finn on the Fly is the story of Ben and his best friend, Finn, a border collie with a flair for making friends. Ben isn't so lucky. He's desperate to make friends at his new school but lacks the confidence to do it, until the outgoing Finn gets his nose in a mad science experiment that spurs a series of crazy events that change their lives forever.
Vampire Dog : Ace (Collin MacKechnie) is just like any other new kid at school, until he inherits Fang (voiced by Norm MacDonald), his grandfather's Transylvanian dog. Fang, however is no ordinary canine.
Chihuahua Too!, Charlie a Toy Story, Finn on the Fly, Vampire Dog
"J7920."
Cataloged from container.
DVD release of the 2013 motion picture.
Directed by Morgan Most.
Chaia Mutrux, Zay Harding, Ivy Elfstrom.
Drew Waters, Raymond Ochoa, Rheagan Wallace
Keywords: Chihuahua (Dog breed) -- Juvenile films; Haunted houses -- Juvenile films; Animal ghosts -- Juvenile films; Children's films; Feature films; Juvenile works